Gonioscopy in Practical Ophthalmology: A Comprehensive Review of Its Principles, Practice, and Clinical Relevance - Widyati, Dyah Ratri; Primitasari, Yulia; Komaratih, Evelyn; Nurwasis (Vision Science and Eye Health Journal, 2025)
Introduction: Gonioscopy is a vital ophthalmic examination that enables direct visualization of the anterior chamber angle, which is primarily essential for glaucoma diagnosis and management. Despite being the gold standard, it remains underutilized in clinical practice. Purpose: This review synthesizes current knowledge on gonioscopy's principles, techniques, and clinical relevance, emphasizing its predominant role in glaucoma while acknowledging its broader diagnostic utility. Reviews: Gonioscopy allows detailed assessment of angle structures, which are crucial for distinguishing between open-angle and angle-closure glaucoma and for detecting secondary glaucomas such as neovascular or pigment dispersion glaucoma. Its dynamic indentation capability uniquely differentiates appositional angle closure from permanent synechiae, unlike static imaging modalities. The review highlights historical evolution, technique nuances, indications, and technological advancements, including digital imaging tools. Gonioscopy guides clinical decision-making by identifying angle pathology that influences interventions like laser peripheral iridotomy or surgical procedures. Challenges include operator skill requirements and patient cooperation, with underuse reported even among surgical candidates. Guidelines advocate routine gonioscopic examination for glaucoma suspects. Conclusions: Gonioscopy remains indispensable, especially in glaucoma care, providing dynamic, real-time anatomical insights that cannot be replaced by imaging alone. Improving clinical training and integration into routine practice is critical to optimize early detection, accurate diagnosis, and tailored management of glaucoma and other anterior segment disorders.